2019
DOI: 10.1016/j.neuroimage.2018.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous LAMC3 mutation links to structural and functional changes in visual attention networks

Abstract: The occipital lobe contains a substantial part of the neural machinery involved in visual perception. Mutations in the LAMC3 gene have recently been shown to cause complex bilateral occipital cortical gyration abnormalities. However, to what extent these structural changes impact visual behavior is not known. We recorded responses for two screening test batteries targeting visual function (Leuven - Perceptual Organization Screening Test, Cortical Vision Screening Test) and measured eye fixation performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 105 publications
1
17
0
Order By: Relevance
“…In skin, LAMC3 was expressed in the basement membrane at the dermal-epidermal junction of the nerve penetration points [ 17 ]. Some studies have demonstrated that LAMC3 mutation is linked to changes in the structure and function of the visual attention network [ 44 ], which modulates astrocyte migration and angiogenesis by modulating the activation of retinal microglia. LAMC3 was essential for retinal layered photoreceptor organization, and synaptic stability [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In skin, LAMC3 was expressed in the basement membrane at the dermal-epidermal junction of the nerve penetration points [ 17 ]. Some studies have demonstrated that LAMC3 mutation is linked to changes in the structure and function of the visual attention network [ 44 ], which modulates astrocyte migration and angiogenesis by modulating the activation of retinal microglia. LAMC3 was essential for retinal layered photoreceptor organization, and synaptic stability [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this wider—though weaker—expression also in the frontal cortex, one individual with generalized polymicrogyria also extending to parietal and frontal lobes was reported (Zambonin et al, 2018). Of note, in one of the initially reported individuals (Barak et al, 2011), voxel‐based morphometry and structural connectivity analysis later also indicated impaired cortical areas beyond the occipital lobes (Urgen et al, 2019). While the classification of cortical malformation as polymicrogyria in the herewith reported individual fits to the previous reports, she is the only one with spared occipital lobes and polymicrogyria being present in the frontal lobes only.…”
Section: Discussionmentioning
confidence: 99%
“…LAMC3 has diverse roles in cell migration, apoptosis and adhesion, and variants within this gene have been found to contribute to cortical malformations [5052]. It has been reported that individuals with these variants also have specific behavioural outcomes, e.g., impairments in endogenous attentional processes [51], which collectively suggests that these data may have biological relevance to the CP phenotype.…”
Section: Discussionmentioning
confidence: 99%